Black hairy tongue: a case series - Yasemin Korkut; Nazlı Dizen Namdar (SERNEV, 2017)
Introduction: Black hairy tongue occurs as a result ofinability desquamation and hyperthrophy of filiforme papilla on the dorsum ofthe tongue which also cause as the creation of velvety plaques.CasePresentation:Four patients with black hairy tonguewho were referred to our clinic with different complaints were presented ascases. Discussion: Althoughthe etiopathogenesis of the black hairy louse is not completely known, manypredisposing factors have been proposed. Prevention of triggering factors, theregulation of food and water, mechanical cleaning of the language is importantin the treatment of black hairy tongue. Medical treatment includes antisepticsolutions, topical tretinoin.Conclusion: Family physicians should consider that infirst-stage smokers patients may rarely develop black hairy language.